Measuring risk of attack on bus networks - O'MAHONY, MARGARET MARY (My University, 2008)
Public transport systems are at risk from attacks as they are open, dynamic systems carrying large numbers of people. Although attacks have been carried out on public transport since the 1920?s, the nature of attacks has changed in recent years and the objective of many terrorist attacks is to cause large number of casualties and create major disruptions on the network. The research examines the risk from such an attack on the bus network in Dublin. As part of the research, a framework was developed which can be used to calculate risk using a number of factors which were chosen to take into account the attractiveness of the target, the overall threat and the level of disruption caused. The factors were grouped into static factors (factors that remain largely unchanged) and dynamic factors (factors which change due to further factors such as time). These factors were weighted using the Analytic Hierarchy Process (AHP). Eleven bus routes throughout Dublin were chosen and were analysed under five different scenarios. The research concluded that rush hour and when the buses are operating at high load factors are particularly high risk situations but in off-peak hours the number of possible targets on a route may still mean the risk is relatively high during those times. Limited options are available to mitigate those risks although rerouting during periods of medium to high alert offers some possibility of offsetting the risks of attack.
Procs of 87th Annual Meeting of the Transportation Research Board
PUBLISHED
Washington D.C.
Keywords: Public transport - Ireland; assault; Bus routes - Dublin; Crime risk - Dublin